A Financial and Economic Appraisal of Capital Investment in Jijiga Export Slaughter House, Somali Region, Ethiopia, Using FAST Modeling Standards - Esfahani, Amirreza Botlani (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
This paper presents a financial and economic appraisal of an investment for the construction of a slaughterhouse facility in Faafan village, Somali region, Ethiopia. Sustained political unrest has hampered private-sector activity in the region. As such, this first-mover investment could be critical to attract more capital to the region if successful. Success of this project can be a turning point for the region and new investments can take the area out of the economic backwardness. The financial modeling undertaken in this study is based on the FAST (Flexible, Appropriate, Structured, and Transparent) approach, which increases model readability and decreases the incidence of error. This is followed by an integrated economic and beneficiary analysis. An important conclusion is that the project will generate significant FNPV and ENPV (US$ 9.42 million and US$ 65.32 million, respectively), sufficient to attract other investors to the Somali region. A positive ENPV indicates that in addition to being of benefit to pastoralists, the presence of a commercial slaughterhouse facility will be helpful to the broader, national economy. On the other hand, first-mover status means that the facility has assumed a number of risks in isolation, including local resistance, regional instability, and foreign-market risk. The project stakeholders comprise of the private investor, smallholder livestock producers, livestock traders, slaughterhouse workers, the Faafan village community, and the Government of Ethiopia, who are also major project beneficiaries. Keywords: financial and economic analysis, FAST modeling, Somali region, Slaughterhouse, FNPV, ENPV

ÖZ: Bu calisma Etiyopyada, Somali bölgesinde Faafan köyünde, bir kesimhane kurmak üzerine önerilen yatirim´in mali ve ekonomik degerlendirmesini yürütmektedir. Bu alanda özel sektörün bölgesel gelismesi siyasiden gelen huzursuzluklar tarafindan engellendi. Somali bölgesinde ilk nakliye yapan kesimhane budur. Bu alanda olasi bir basari bölgeye daha fazla sermayeyi cekmek acisindan kritik bir yatirim olarak görülmektedir. Bu projenin basarisi bu bölge icin bir dönüm noktasi olabilir ve yeni yatirimlari ile bu bölgeyi ekonomik kriz´den kurtarabilir. FAST modelleme yaklasimi entegre edilmis ekonomik ve yararlanici analizi ile birlikte finansal modellemesini tamamlamak icin kullanimdadir. FAST (Esnek, Uygun, Yapisal, ve Seffaf) standartlari modellerin okunabilirligini gelistirmeyi ve ayni zamanda hata oranini düsürmeyi amaclayan bir kurallar dizisi´dir. Bu calismanin en önemli sonuclarindan biri projenin Somali bölgesinin diger yatirimcilarinin ilgisini cekebilecek büyük miktarda olan FNPV ve ENPV´sidir. (FNPV ABD$ 9.42 Million Dolar ve ENPV ABD$ 65.32 Million Dolar´dir.) Diger tarafta bölgenin ilk nakliyecisi olarak bu kesimhane insanlarin olumsuz yaklasimi ve Somali bölgesinin degiskenligi gibi bir cok risk faktörlerinin üstesinden gelmesi gerekmektedir. Cikan sonuclara göre ENPV olumlu gözükmektedir. Göcebe cobanlarina avantaj saglamasi yani sira, ticari kesimhanenin varligi tüm ülkenin ekonomisi icin faydali oldugunu gösterir. Proje paydaslarin´in birkac gruplari vardir: özel yatirimci, kücük ölcekli hayvancilik üreticileri, ve hayvancilik tüccarlari, kesimhane calisanlari, Faafan köy halki ve Etiyopya hükümeti. Anahtar kelimeler: mali ve ekonomik degerlendirme, FAST modelleme, Somali bölgesi, kesimhane, FNPV, ENPV, paydasla
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2016. Supervisor: Prof. Glenn Paul Jenkins.
Keywords: Banking and Finance; Banks and Banking - Somalia; Financial and economic analysis; Somali region; Slaughterhouse; FNPV; ENPV; FAST modeling